Design and Construction of an Improvised Vertical Axis Wind Turbine. - Owamaani, Babrah (Kabale University, 2024)
The use of wind energy for energy generation is one of the oldest methods for harnessing renewable energy. The use of renewable energy is an essential ingredient of socio-economic development and economic growth. Renewable energy sources such as wind energy, are abundant and can help in reducing the dependency on fossil fuels. Increased concern for the environment nowadays led to research for more environment-friendly sources of energy and with these considerations, wind energy can be considered a viable option in this regard. Different configurations of wind turbines such as horizontal axis wind turbines and vertical axis wind turbines are mainly used for energy extraction. The horizontal axis is mainly used in large-scale applications and thus its implementation is generally a concern due to the huge installment setup and initial cost; whereas vertical axis wind turbines offer promising solutions for smaller rural areas or medium-sized residential spaces. Energy generation from wind turbines will surely be affected by the geometry of the blade it is using and its orientation in the turbine. For effective use of turbine, both parameters should be optimally set and determined. This review work focuses on various stages for the design and development of optimized vertical axis wind turbines. Project work included the Optimization of design parameters of vertical axis turbine blades considering different parameters such as geometry orientation in assembly.